MEMAHAMI TEKS ALQURAN DENGAN PENDEKATAN HERMENEUTIKA (Sebuah Analisis Filosofis) - Marhaban Marhaban (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2017)
This article discusses understanding the Qur'anic text with a hermeneutic approach to a contemporary approach that offers a new approach to interpreting the Qur’an (philosophically). In this hermeneutic approach the texts of the Qur'an do not stand alone, but are very dependent on the surrounding context, which includes text, context, and contextualization. The existence of hermeneutics with its own methodology brings a new nuance in the interpretation of the Qur'an. With this method the Qur’an is no longer considered as something sacred, because in the eyes of hermeneutics when the text descends and is in the midst of the reality of human life, it is fully owned by humans and has the right to be interpreted, internalized, and understood whatever it wants. Everything contained in the text, for hermeneutics, can be interpreted and understood its meaning clearly. And this is what distinguishes it fundamentally from the theme of interpretation in the Ulumul Quran discourse